2013
DOI: 10.1002/ange.201209093
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of β‐Amino Nitriles through a ScIII‐Catalyzed Three‐Component Mannich Reaction of Silyl Ketene Imines

Abstract: Chiral b-amino nitriles are versatile synthetic intermediates that are readily transformed into optically active compounds such as b-amino acids, and 1,3-diamines. [1] The asymmetric addition of alkyl nitriles to imines provides a straightforward route to such compounds. [2] Although many methods for the asymmetric Mannich reaction have been described, [3] the use of less nucleophilic alkyl nitriles as the nitrile species is a continuing challenge; [4][5][6] one reason for this issue is the poor acidity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 91 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…In our previous work, privileged N,N'-dioxide ligands (Figure 1) frequently show wide substrate generality and ex-ceptional levels of stereocontrol for a number of asymmetric reactions. [10,11] For example, KR of racemic 2-arylcyclohexanones through chiral N,N'-dioxide-scandium(III)-complex-catalyzed asymmetric Baeyer-Villiger oxidation was accomplished in high efficiency with an abnormal migratory aptitude. [11a] Furthermore, we found that chiral N,N'-dioxide-metal complexes were capable of acting as chemo-and enantioselective sensors [12] for fluorescent recognition of racemic a-hydroxycarboxylic acids, [12a] amino alcohols, [12b] and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, privileged N,N'-dioxide ligands (Figure 1) frequently show wide substrate generality and ex-ceptional levels of stereocontrol for a number of asymmetric reactions. [10,11] For example, KR of racemic 2-arylcyclohexanones through chiral N,N'-dioxide-scandium(III)-complex-catalyzed asymmetric Baeyer-Villiger oxidation was accomplished in high efficiency with an abnormal migratory aptitude. [11a] Furthermore, we found that chiral N,N'-dioxide-metal complexes were capable of acting as chemo-and enantioselective sensors [12] for fluorescent recognition of racemic a-hydroxycarboxylic acids, [12a] amino alcohols, [12b] and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Low catalyst loadings (10 mol%) are common, but a broad spectrum of Lewis acid catalysts are effective, especially those with N,N 0 -dioxide [157][158][159], Schiff base [160][161][162], and phosphine ligands [163][164][165][166][167][168]. The use of ortho-hydroxyaniline has been developed as an effective template for in situ imine formation that, following asymmetric condensation, can be easily removed (Scheme 35) [159]. Analogous to the asymmetric tandem aldolMichael reactions (Scheme 34) are the asymmetric tandem vinylogous MannichMichael reactions of α,β-unsaturated-γ-butyrolactams with nitrovinyl compounds using a novel dinuclear nickel catalyst (Scheme 36) [161].…”
Section: Mannich Reactionsmentioning
confidence: 99%
“…Thus, alternative methods for generation of acyclic tetrasubstituted enolates or their synthetic equivalents have been developed. [58] Noteworthy among these, a highly stereoselective carbocupration of chiral ynamides followed by oxidation of the resultant vinylcuprate has been developed by Marek and co-workers.. [8] Nevertheless, the development of a simple, highly stereocontrolled method for synthesis of stereochemically defined tetrasubstituted enolates from readily available achiral starting materials remains an important objective. Toward this end, we report herein a simple procedure by which stereodefined tetrasubstituted enolborinates are generated with exceptional stereoselectivity via 1,4-hydroboration reactions [9,10] of unsaturated morpholine carboxamides with (diisopinocampheyl)borane ((Ipc) 2 BH), and demonstrate that the tetrasubstituted enolborinates undergo highly enantio- and diastereoselective aldol reactions with representative achiral aldehydes.…”
mentioning
confidence: 99%
“…[2] To the best of our knowledge, stereodefined tetrasubstituted enolates have not been successfully generated with high stereochemical control by using alternative reductive aldol procedures, [9,10,12,13] but several have been generated by 1,4-addition of organometallic reagents to unsaturated carbonyl derivatives. [5m,q,r,14] …”
mentioning
confidence: 99%
See 1 more Smart Citation